AI-powered marketing automation: exploring the factors affecting implementation in a large company - Vihavainen, Silja (2024)
Marketing automation has firmly established itself as a necessary technology in marketing, and artificial intelligence (AI) seems to introduce novel opportunities to enhance the system even further. Integrating AI and marketing automation creates benefits for marketing, such as more efficient data processing, predictive analytics, automated targeting, and improved optimization of content and channels. Therefore, this study aims to increase the understanding of AI-powered marketing automation and its implementation. The objective is achieved through a case study conducted in a large company implementing an AI-powered marketing automation system to replace its previous system. The theoretical foundation encompasses literature reviews on marketing automation, AI in marketing, and marketing technology implementation. The findings of this study illustrate how AI changes the different features of marketing automation and explain the concept and operational logic of AI-powered marketing automation. Furthermore, the study identifies the factors that enable or impede its implementation in the planning, communication, and evaluation phases. The findings highlight employees’ central role in AI-powered marketing automation implementation. In addition to technical and analytical competence, the system requires employees to trust that AI’s algorithms can allocate the optimal content to the right customers in the right channel at the right time. Additionally, the study proves that customer data is another critical factor supporting AI-powered marketing automation implementation. The system needs a vast amount of quality customer data to operate optimally and provide accurate personalization. Therefore, data management processes should support the implementation. This study contributes to the knowledge of AI-powered marketing automation systems by identifying the factors that should be considered during the implementation. It also offers practical insights for businesses planning to harness AI into their strategic marketing execution.